Tourism and Sustainability: Exploring the Role of AI-Driven Tourism Practices in Shaping Consumer Sustainable Behaviour - Grumadaitė, Kristina; Babu, Sebin Thomas; Jose, Sonny (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
The actors of the tourism industry worldwide keep implementing more digital solutions into the tourism services, including artificial intelligence (AI) tools to improve travel planning, pricing, marketing and other business functions, and to increase the quality of tourism experience. Sustainability, on the other hand, is of significant importance in order to maintain economic efficiency, social equity and ecological consideration. However, various gaps and inconsistencies between providing and using AI and sustainable tourism services are noticed. Thus, this paper aims to analyse the scope of cohesion between AI application and sustainability practices in the sector. The exploratory empirical research revealed that AI still plays a limited role in shaping the sustainable behaviour of the consumers of tourism services.